The action of the imagination: Daniel Hack Tuke and late Victorian psycho-therapeutics. (April 2017) - Chaney, Sarah
Histories of dynamic psychotherapy in the late 19 th century have focused on practitioners in continental Europe, and interest in psychological therapies within British asylum psychiatry has been largely overlooked. Yet Daniel Hack Tuke (1827–95) is acknowledged as one of the earliest authors to use the term 'psycho-therapeutics', including a chapter on the topic in his 1872 volume, Illustrations of the Influence of the Mind upon the Body in Health and Disease . But what did Tuke mean by this concept, and what impact did his ideas have on the practice of asylum psychiatry? At present, there is little consensus on this topic. Through in-depth examination of what psycho-therapeutics meant to Tuke, this article argues that late-19 th -century asylum psychiatry cannot be easily separated into somatic and psychological strands. Tuke's understanding of psycho-therapeutics was extremely broad, encompassing the entire field of medical practice (not only psychiatry). The universal force that he adopted to explain psychological therapies, 'the Imagination', was purported to show the power of the mind over the body, implying that techniques like hypnotism and suggestion might have an effect on any kind of symptom or illness. Acknowledging this aspect of Tuke's work, I conclude, can help us better understand late-19 th -century psychiatry – and medicine more generally – by acknowledging the lack of distinction between psychological and somatic in 'psychological' therapies.